The Regulatory Record of the Greenspan Fed - Calomiris, Charles W (American Economic Review, 2006)
Just describing how the Federal Reserve made possible the expansion of commercial banks’ powers to permit them to engage in investment banking could occupy this entire essay. That change occurred in several stages, beginning with the Fed’s decision in 1987 to allow small inroads by banks into investment banking. Those changes created a favorable track record, which laid the groundwork for the Administration’s and Congress’s willingness to eliminate restrictions entirely in 1999. Can one identify a “philosophy of regulation” that underlies the regulatory advocacy of the Fed under Chairman Greenspan? Although the Fed’s advocacy on various matters may appear somewhat contradictory or, at least, philosophically heterodox, the Fed has behaved in a manner that is remarkably predictable, once one takes account of the political arena in which both regulatory and monetary policy as made.